2022
DOI: 10.1371/journal.pone.0276331
|View full text |Cite
|
Sign up to set email alerts
|

Poison frog dietary preference depends on prey type and alkaloid load

Abstract: The ability to acquire chemical defenses through the diet has evolved across several major taxa. Chemically defended organisms may need to balance chemical defense acquisition and nutritional quality of prey items. However, these dietary preferences and potential trade-offs are rarely considered in the framework of diet-derived defenses. Poison frogs (Family Dendrobatidae) acquire defensive alkaloids from their arthropod diet of ants and mites, although their dietary preferences have never been investigated. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Sympatric populations of the undefended H. awa and defended E. espinosai (formerly E. darwinwallacei [65]) are both diet specialized, with the former consuming mostly ants and beetles and the latter consuming mostly mites and springtails [66]. In a lab experiment, the defended species D. tinctorius was shown to prefer fruit fly larvae over ants when given the choice [67], suggesting that even in defended species, consumption of possible alkaloid-containing prey is not necessarily a preference. One study found that O. sylvatica alkaloid quantity is inversely correlated with ant and mite stomach contents; however, this species consumed more mites and ants than sympatric H. infraguttatus [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympatric populations of the undefended H. awa and defended E. espinosai (formerly E. darwinwallacei [65]) are both diet specialized, with the former consuming mostly ants and beetles and the latter consuming mostly mites and springtails [66]. In a lab experiment, the defended species D. tinctorius was shown to prefer fruit fly larvae over ants when given the choice [67], suggesting that even in defended species, consumption of possible alkaloid-containing prey is not necessarily a preference. One study found that O. sylvatica alkaloid quantity is inversely correlated with ant and mite stomach contents; however, this species consumed more mites and ants than sympatric H. infraguttatus [46].…”
Section: Resultsmentioning
confidence: 99%
“…Sympatric populations of the undefended H. awa and aposematic E. espinosai (formerly E. darwinwallacei [65]) are both diet specialized, with the former consuming mostly ants and beetles and the latter consuming mostly mites and springtails [66]. In a lab experiment, the aposematic species D. tinctorius was shown to prefer fruit fly larvae over ants when given the choice [67], suggesting that even in aposematic species, consumption of possible alkaloid-containing prey is not necessarily a preference.…”
Section: (B) Phases 3 and 4: Passive Accumulation And Active Sequestr...mentioning
confidence: 99%
“…For univariate analysis they have compared quantities or chromatographic peak intensities/areas and performed parametric or non-parametric tests for measuring the significance of this differentiation employing ANOVA and Kruskal–Wallis analysis, respectively (Mina et al 2015 ; Moskowitz et al 2020 ), depending on the data-normality. For multivariate analysis, the main type of analysis used has been Non-metric multidimensional scaling (NMDS) accompanied by ANOSIM or PERMANOVA analysis for testing the significance of different metavariables in differentiating alkaloid profiles (Saporito et al 2006 , 2007 , 2010 ; Stuckert et al 2014 ; Mina et al 2015 ; Moskowitz et al 2022 ). Correlation analysis have also been tested for measuring the strength of the correlation between total amount of alkaloids and diversity of alkaloids (Saporito et al 2010 ), a common pattern found on different species.…”
Section: Discussionmentioning
confidence: 99%